Taxonomic and phylogenetic characterizations of Keissleriella bambusicola sp. nov. (Lentitheciaceae, Pleosporales) from Yunnan, China - Jiang, Hong-Bo; Phookamsak, Rungtiwa; Doilom, Mingkwan; Mortimer, Peter E.; Xu, Jian-Chu; Lumyong, Saisamorn; Hyde, Kevin D.; Karunarathna, Samantha C. (Phytotaxa, 2019)
Keissleriella bambusicola sp. nov., collected from Yunnan Province in China, is described and illustrated in this paper. The new taxon was well placed in the genus Keissleriella based on subglobose to ampulliform, uni- to bi-loculate ascostromata with an ostiole covered by dark setae, 8-spored, bitunicate, fissitunicate, cylindrical to cylindric-clavate asci and yellowish brown, ellipsoidal to cylindrical (4–)5(–6)-septate ascospores. Keissleriella bambusicola is introduced based on a comparison of the morphological characteristics of morphologically (K. rosae, K. taminensis, K. yonaguniensis) and phylogenetically (K. caraganae, K. yonaguniensis) closely related taxa. The species can be distinguished from the above mentioned species in having uni- to bi-loculate, raised, superificial ascostromata and (4–)5(–6)-septate ascospores. Maximum likelihood and Bayesian inference analyses based on the combined LSU, SSU, TEF1-α and ITS sequence dataset showed that our new taxon forms a sister lineage, with K. caraganae and clustered with K. yonaguniensis in the genus Keissleriella. In addition, Keissleriella is reported on bamboo for the first time.